Formation of geographical concepts competency-based approach to learning geography of Ukraine (Pedagogy of Higher and Secondary Education, 2013)
Trosyuk S. D. Formation of geographical concepts competency-based approach to learning geography of Ukraine.The article deals with the gradual process of the formation of concepts geografichsekih competency-based education campaign to geographic Ukraine. The structural constructs in forming the content of geographical concepts in the process of learning ce geographic Ukraine at the level of phenomena, concepts and relationships. Are examples of exercises in order to create jobs geographical competence competency-based approach.
Keywords: geographical concepts; competence-based approach; students osnvonoy schools; natural history items